Novel’s Marketplace Website - Syed Anuar, Syed Muizzuddin; Mohamed, Rozlini (Applied Information Technology And Computer Science, 2025)
The Novel’s Marketplace Website project addresses the emerging need for a centralized platform in the digital literary landscape that focusing on the fragmented nature of novel e-commerce, review and interactions within the reader community. The main reason of this development is because of the challenges in the current system, including no dedicated platform exclusively for buying and selling that focus on novels and limited accessibility and inclusivity. The project aims to develop a comprehensive, user-centric website for sharing literary insights, experiences and facilitating the buying and selling of novels that involves buyer and seller of novel’s enthuasists. By applying an object-oriented approach and modern web technologies, this projects develops a web-based platform tailored to the preferences of novel enthusiasts. The methodology involves the design and implementation of key features such as user registration, log in, seller management, novel cataloging, purchase and payment, review submission, report management. The outcome is a novel’s marketplace that effectively involves novel reviews, enhances user interaction, and provides an inclusive platform for both readers and sellers. This website has significantly improved accessibility, user engagement and the quality of literary discourse. The project paves the way for future enhancements in online literary communities, suggesting areas for further research in user experience optimization and community-driven features. The Novel’s Marketplace Website stands as a testament to the potential of digital platforms in transforming literary engagement and fostering a vibrant, inclusive community of novel lovers.